Faces of Anonymity
IX, 260 p.
Keywords: This pathbreaking collection of original essays surveys an important but neglected topic: anonymous publication in England for the Elizabethan age to the present. An impressive group of scholars analyzes a wide range of literary phenomena including: Shakespeare in 17th century commonplace books; the phrase 'By a Lady'; the implied author of an eighteenth century queer fiction; Bentley and the battle of books; essays by Equiano (?); the novel, 1750 - 1830; Frankenstein's unnamed monster; the co-authored pseudonym Michael Field; nineteenth century ghostwriting; and a postmodern hoax on national identity. The editor's introduction places the essays within the context of the historical trajectory of anonymous authorship. Essential reading for anyone interested in authorship and the history of the book.